Rational construction of novel strontium hexaferrite decorated graphitic carbon nitrides for highly sensitive detection of neurotoxic organophosphate pesticide in fruits. (1st March 2021) - Rajaji, Umamaheswari; Chinnapaiyan, Sathishkumar; Chen, Tse-Wei; Chen, Shen-Ming; Mani, G.; Mani, Veerappan; Ali, M. Ajmal; Al-Hemaid, Fahad M.A.; El-Shikh, M. Suliman
Abstract: As a growing aspect of agriculture purposes, an extensive number of pesticides and insecticides that have been used to produce yield, and particularly, through toxic organo-pesticides and herbicide. Moreover, the long-term usage of organo-pesticides leads to health problems, which causes serious health threat to human beings. Therefore, monitoring the level of organo-pesticides in food products is highly essential for practical applications to ensure food safety. Herein, we successfully synthesized strontium hexaferrite (nanorods) decorated on porous graphitic carbon nitride (SrFe12 O19 /g-C3 N4 ) electrocatalyst through the incorporation of metal precursors such as strontium nitrate, ferric nitrate, melamine and glucose via a facile hydrothermal process with excellent electrochemical performance towards the detection of fenitrothion (FTN). The structural and chemical features of the as synthesized SrFe12 O19 /g-C3 N4 electrocatalyst were characterized by various spectroscopic and analytical methods. The SrFe12 O19 /g-C3 N4 /SPCE shows a most-improved electrocatalytic performances compared to other modified and unmodified SPCEs. Mainly, the SrFe12 O19 NRs were highly interconnected with the g-C3 N4 matrix, which provides a sufficient electrocatalytic ability for the rapid electrochemical performances and it has achieved higher BET surface area of 325 m 2 /g. Moreover, our proposed electrochemical sensor performs a good detection range from 0.005 to 378.15  μ M with a low detection limit of 0.0014  μ M (S/N=3) and sensitivity of the modified sensor is 19.23 μ A μ M −1 cm −2 . The practicality of the proposed SrFe12 O19 /g-C3 N4 modified sensor was manifested by the profitably determination of FTN in various fruits samples with acceptable recoveries. Graphitic abstract: A Simple and Rapid Fabrication of SrFe12 O19 /g-C3 N4 /SPCE and Versatile Platform for Sensing of Organophosphate Pesticides in Fruits Image, graphical abstract